LEGAL UNCERTAINTY IN GOVERNMENT REGULATION NUMBER 51 OF 2020 REGARDING THE TEN-YEAR PASSPORT VALIDITY PERIOD - Diatmika, Komang Trisna; Sara, Rineke (International Journal of Social Service and Research, 2024)
This study examines the legal uncertainty arising from the implementation of Government Regulation No. 51 of 2020 concerning the change in passport validity from 5 years to 10 years, as well as the need for legal reform to address the issue. Legal uncertainty occurs due to the absence of clear implementing regulations, thus affecting the effectiveness of policy implementation in the field of immigration administration, including tariff adjustments and management of passport forms. The purpose of this study is to analyze the lack of clear implementing regulations and their impact on immigration administration, proposing solutions such as creating comprehensive guidelines, legal harmonization, and system updates to ensure policy execution. This research utilizes the normative method to analyze the legal uncertainty surrounding Government Regulation Number 51 of 2020 by examining the relevant legal standards. This study finds that the enactment of Government Regulation No. 51 of 2020 has created legal uncertainties, particularly regarding the transition for existing passports, fee adjustments, and administrative procedures. These ambiguities may disrupt immigration services and confuse both the public and immigration officers, calling for clear guidelines and implementing regulations to ensure the smooth execution of the policy. This study recommends legal reform by preparing comprehensive implementing regulations, harmonization with related laws, and updating the administrative system to support policy implementation. This study suggests a more adaptive legal framework and increases the capacity of technology and human resources to face future immigration challenges.